Management of Educational Philanthropic Institutions in LAZISMU Yogyakarta: A Comprehensive Analysis - Dela Eka Putri A; Muhammad Dalhar; Arifah Nurrahmawati; Fia Nur Azizah; Mohammad Ghalil Gibran; Silviana Siswanda (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2023)
Purpose – The purpose of this research is to explore the management and operation of educational philanthropic institutions within LAZISMU, Yogyakarta, focusing on fund management and distribution to the community. It also aims to investigate LAZISMU's historical background, mission, principles, and its role in addressing socio-economic challenges in Indonesia. Design/methods– The study employed a qualitative research approach, conducted as a field study at LAZISMU's premises in Yogyakarta. A descriptive research design was used to depict the current state and activities at LAZISMU. Data collection methods included observation, interviews, and documentation, ensuring comprehensive and authentic insights. The primary data collection occurred on March 20, 2023, at LAZISMU's office, with Mr. Nugroho as the key informant. Findings – The study reveals the historical background of LAZISMU, its mission, principles, and its crucial role in addressing socio-economic challenges in Indonesia. LAZISMU is recognized as a national-level zakat institution, founded in 2002 by the Central Board of Muhammadiyah and reaffirmed through various legal decrees. It operates with a commitment to professionalism, transparency, and innovation, with a focus on six pillars covering various aspects of socio-economic development. These pillars encompass social, humanitarian, health, education, economic, and environmental dimensions. LAZISMU's inclusive approach, involving collaboration with government, individuals, and banks, has contributed to its effectiveness. The study also highlights LAZISMU's role in promoting digital literacy and ethics in Islamic education. Research implications/limitations – Implications include the need for curriculum integration of digital literacy and ethics in Islamic education, as well as the importance of adapting to the digital era responsibly. However, the study's limitation lies in its focus on a single institution, which may affect the generalizability of the findings. Future research should extend to multiple Islamic educational settings and consider longitudinal studies to provide a more comprehensive understanding of the impact of digitalization on Islamic education, encompassing traditional teaching methodologies and spiritual development. Practical implications – Practical implications include the potential for other educational philanthropic institutions to learn from LAZISMU's successful practices in fund management, transparency, and collaboration with various stakeholders. It also underscores the importance of integrating digital literacy into Islamic education curricula to prepare students for the digital era. Originality/value – This research contributes to the existing body of knowledge by providing insights into the management of educational philanthropic institutions within LAZISMU, Yogyakarta, and its role in promoting digital literacy in Islamic education. It offers valuable information for academics, policymakers, and educational institutions interested in philanthropic initiatives and the adaptation of Islamic education to the digital age.